A "Team of Three" Practicum Standard for Emerging Coaches and Sport Psychology Practitioners. (4th July 2019) - Vento, Kaila A.; Madrigal, Leilani; Vargas, Tiffanye M.
Abstract : The transitioning from student to coach or sport psychology practitioner requires sufficient training and practice. A well-crafted and organized program allows for professional growth and promotes career and field development. It also prepares students in sport team relationships and mental-skills training. Based on a coach's experience, this article introduces a "team of three" practicum standard, consisting of a supervisor, a lead consultant, and a junior consultant to teach and develop students as coaches and sport psychology practitioners. Suggestions on how to incorporate this standard into educational programs are provided.